RIGHTEOUS OR OUTRAGEOUS: A STUDY OF THE REPRESENTATION OF THE WORD MUSLIM IN AUSTRALIAN NEWS WEBSITES : A CRITICAL DISCOURSE ANALYSIS - Maya Sofiana Utami, - (2012)
Entitled "Righteous or Outrageous: A Study of The Representation of Muslim in Australian News Websites (A Critical Discourse Analysis)", the present study aims to unveil how Australian news websites portray Muslim in terrorism context. Seventeen news texts related to terrorism issue were selected from several Australian news websites published between 2006 - February 2011. This study applied Fairclough's (2003) notion of representation of social events to investigate the representation of Muslim and the ideology behind it. Hardt-Mautner's (1995) conception on combining CDA and corpus were also employed to support the findings. The results revealed that words with bad connotation often appeared with the word 'Muslim(s)' and that Material Process dominating in the texts. Some of the material processes are words with negative semantic load. With those findings it can be concluded that Australian news websites potentially has anti-Muslim ideology since Muslim was often related to the terror attact reported in the news and the word 'Muslim(s)' mostly collocated with 'negative words'.